2005
DOI: 10.1110/ps.051671705
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an acylase active on cephalosporin C

Abstract: Semisynthetic cephalosporins are synthesized from 7-amino cephalosporanic acid, which is produced by chemical deacylation or by a two-step enzymatic process of the natural antibiotic cephalosporin C. The known acylases take glutaryl-7-amino cephalosporanic acid as a primary substrate, and their specificity and activity are too low for cephalosporin C. Starting from a known glutaryl-7-amino cephalosporanic acid acylase as the protein scaffold, an acylase gene optimized for expression in Escherichia coli and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 21 publications
(36 reference statements)
5
87
0
Order By: Relevance
“…But the 7-ACA, intermediate and byproduct probably inhibited the catalysis with the extension reaction time. Pollegioni found that the mutant H296S/H309S of cephalosporin C acylase from N176 had the improved product inhibition [5]. In this research, after 15 minutes, A12 perhaps was inhibited by the 7-ACA or byproduct produced numerously due to the mutation of S471ÎČ.…”
Section: -Aca Productivity With One-step Process Catalyzed By A12mentioning
confidence: 62%
See 1 more Smart Citation
“…But the 7-ACA, intermediate and byproduct probably inhibited the catalysis with the extension reaction time. Pollegioni found that the mutant H296S/H309S of cephalosporin C acylase from N176 had the improved product inhibition [5]. In this research, after 15 minutes, A12 perhaps was inhibited by the 7-ACA or byproduct produced numerously due to the mutation of S471ÎČ.…”
Section: -Aca Productivity With One-step Process Catalyzed By A12mentioning
confidence: 62%
“…Researchers tried to separate cephalosporin C acylase from the micro-organisms that could convert CPC into 7-ACA directly [4]. One-step enzymatic method achieved an annual product value 400 million U.S dollars in the global market [5]. It was the biggest obstacle that the cephalosporin C acylase catalyzed the CPC to 7-ACA directly in a very low efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR products (full-length plasmids) were used to transform JM109 E. coli cells (the cloning host strain); the plasmid DNA was then pooled and transferred to BL21(DE3)pLysS E. coli cells (the expression host strain); recombinant cells were used for the screening procedure as detailed below. For each position,~280 clones were screened (Table 5), a number that gives a probability of 96% that every single amino acid is introduced at the desired position [30], and 10 clones were sequenced to verify the mutagenesis efficiency. The introduction of the mutations was confirmed by automated DNA sequencing.…”
Section: Site-directed and Site-saturation Mutagenesismentioning
confidence: 99%
“…The activity of J1 acylase was determined by a spectrophotometric method as described in [19,20], with slight modifications. Equal volumes (125 ll) of enzyme and substrate (GL-7-ACA) were allowed to react in a Thermomixer (Eppendrof) at 37°C for a certain period of time before the reaction was terminated by the addition of 1 ml mixture of 20% acetic acid and 0.1 M sodium hydroxide.…”
Section: Enzyme Kineticsmentioning
confidence: 99%